Pillars of customer retention: an empirical study on the influence of customer satisfaction, customer loyalty, customer profitability on customer retention - Almohaimmeed, Bader (Serbian Journal of Management, 2019)
The aim of this study is to explore relationships among five factors: customer relationship management, customer satisfaction, customer loyalty, customer profitability, and customer retention. The sample of the study consists of 750 managers and employees of different restaurant in Riyadh, the capital city of Saudi Arabia. The questionnaire developed for the purpose of this study is distributed by hand to respondents. Out of 750 questionnaires distributed, 497 are returned with a high rate of response. The Analysis of Moment Structures (AMOS, Version 22) is used to analyze the collected data. The findings of the study revealed a significant influence of customer relationship management on customer satisfaction, a significant influence of customer satisfaction on both customer loyalty and customer profitability. Therefore, the data doesn’t support the hypothesis that customer loyalty mediates the relationship between customer satisfaction and customer profitability. On the other hand, there are significant relationships between customer satisfaction and customer profitability and between customer profitability and customer retention, while there is no significant relationship between customer satisfaction and customer retention.